Cymbella liangyanlingii sp. nov. (Bacillariophyta, Cymbellaceae), a new diatom species from the upper tributary of Liujiang River, Guangxi Zhuang Autonomous Region, China - Tang, Zheng-Bin; Guo, Ji-Shu; Ni, Hong-Ping; Xiao, Qiao-Zhi; Kociolek, John Patrick; Li, Yan-Ling (Phytotaxa, 2024)
Cymbella liangyanlingii sp. nov. was collected from epilithic samples in the Liujiang River, Guangxi Zhuang Autonomous Region, China. Light microscopy (LM) and scanning electron microscopy (SEM) were used to describe the morphology of the new species, and in addition we provided detailed ecological information about this species. C. liangyanlingii sp. nov. has the features that assign it to the genus Cymbella, including the terminal raphe fissures deflected toward dorsal margin, apical pore fields present at each end on the valve and, for most taxa in the genus, one or more stigmata on the ventral side of the central area. The key diagnostic features that easily distinguish the new species from other similar species: 1) the inconspicuous central area, 2) three slit-like stigmata on the ventral margin, 3) the striae have no interruption on the valve margin, and 4) striae that are mostly uniseriate in the middle and biseriate (5–7) in the ends. This combination of features distinguishes C. liangyanlingii sp. nov. from congers such as C. liyangensis, C. distalebiseriata, C. alexandrovichii and C. hubeiensis. These findings can help us further understand the morphological and ecological information of the genus Cymbella in China.